Tree species diversity of UiTM Jengka forest reserve (line 8: 9 and line 19: 20) / Nor Rosidah Osman and Mastura Jafar - Osman, Nor Rosidah; Jafar, Mastura (2009)
The UiTMJFR is a forest reserve in Pahang with about 250 acres. A research was done to study the tree species diversity of UiTM Jengka Forest Reserve (UiTMJFR). This study area at line 8:9 and line 19:20. This study was conducted in two transect with size plot 10 X 100m each. Total of the species has been found is categorized based on measuring diameter breast height (DBH) is 10cm and above. There are 84 of trees in the transect one and 56 of trees in the transect two. The trees have being decided to a few of research. These are diameter distribution, biodiversity indices, species richness, habitat, average DBH, and number of dominant for the both transect. Overall, the result for the number of family (21 families), number of species (40 species), and dominant families are Lithocarpus spp and Macaranga spp which have up to 9 trees, and the mean diameter is 19.01cm.